2012
DOI: 10.3324/haematol.2011.060657
|View full text |Cite
|
Sign up to set email alerts
|

Using an age-dependent D-dimer cut-off value increases the number of older patients in whom deep vein thrombosis can be safely excluded

Abstract: BackgroundD-dimer testing to rule out deep vein thrombosis is less useful in older patients because of a lower specificity. An age-adjusted D-dimer cut-off value increased the proportion of older patients (>50 years) in whom pulmonary embolism could be excluded. We retrospectively validated the efficacy of this cut-off combined with clinical probability for the exclusion of deep vein thrombosis. Design and MethodsFive management study cohorts of 2818 consecutive outpatients with suspected deep vein thrombosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 17 publications
11
81
0
4
Order By: Relevance
“…Righini et al (2000) found that the customary D-dimer test could rule out PE in 60% of patients aged<40 years, but in only 5% of patients aged>80. Douma et al (2012) developed a new D-dimer cut-off point in 2818 consecutive outpatients with suspected DVT. The new cut-off value was defined as (patient's age×10) μg/l in patients aged more than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Righini et al (2000) found that the customary D-dimer test could rule out PE in 60% of patients aged<40 years, but in only 5% of patients aged>80. Douma et al (2012) developed a new D-dimer cut-off point in 2818 consecutive outpatients with suspected DVT. The new cut-off value was defined as (patient's age×10) μg/l in patients aged more than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…The question of a higher D-dimer cut-off in elderly patients was raised a decade ago [34], but studies confirming the potential security of such a strategy by retrospectively applying age-adjusted cut-offs to large prospective cohorts of consecutive patients with suspected VTE were published between 2010 and 2012 [35][36][37][38][39]. A recent systematic review and meta-analysis of studies in patients with suspected VTE (PE and DVT) showed a dramatic decrease of the pooled specificity from 66.8% (95% CI 61.3-72) in patients b50 years to 14.7% (95% CI 11.3-18.6) in patients N80 years with the conventional D-dimer cut-off [40].…”
Section: Performance Of D-dimers In the Elderlymentioning
confidence: 99%
“…Ancak testin pozitif olması DVT tanısı ile birlikte diğer tanı olasılıklarını da gündeme getirmektedir. Ayrıca ileri yaşlarda ve renal yetmezlik durumunda D-dimer seviyesinde artış olduğu da bilinmektedir [7,21]. Bizim yaptığımız çalışmada ise, orta ve yüksek olasılıklı PE olan hastalarda ortalama D-dimer düzeyleri, PE olmayan ve düşük olasılıklı gruba göre daha yüksek bulunmuş olmasına rağmen istatistiksel olarak anlamlı değildi.…”
Section: Bulgularunclassified